2019
DOI: 10.1136/tobaccocontrol-2018-054584
|View full text |Cite
|
Sign up to set email alerts
|

Have e-cigarettes renormalised or displaced youth smoking? Results of a segmented regression analysis of repeated cross sectional survey data in England, Scotland and Wales

Abstract: ObjectivesTo examine whether during a period of limited e-cigarette regulation and rapid growth in their use, smoking began to become renormalised among young people.DesignInterrupted time-series analysis of repeated cross-sectional time-series data.SettingGreat BritainParticipants248 324 young people aged approximately 13 and 15 years, from three national surveys during the years 1998–2015.InterventionUnregulated growth of e-cigarette use (following the year 2010, until 2015).Outcome measuresPrimary outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 24 publications
2
44
1
4
Order By: Relevance
“…For example, as most adult e-cigarette use is among adults who smoke or have recently given up [7][8][9]18,19], it logically follows that most children whose parents use e-cigarettes will come from families where they are currently, or have recently also been, exposed to tobacco cigarettes. Analyses of survey data from three UK nations found that experimentation with tobacco cigarettes declined during the emergence of e-cigarettes, while the decline in perceptions of acceptability of smoking accelerated [2]. Hence, this provides no evidence that smoking was becoming renormalised during this time and suggests that any gateway effects were not having a population level impact on smoking rates.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…For example, as most adult e-cigarette use is among adults who smoke or have recently given up [7][8][9]18,19], it logically follows that most children whose parents use e-cigarettes will come from families where they are currently, or have recently also been, exposed to tobacco cigarettes. Analyses of survey data from three UK nations found that experimentation with tobacco cigarettes declined during the emergence of e-cigarettes, while the decline in perceptions of acceptability of smoking accelerated [2]. Hence, this provides no evidence that smoking was becoming renormalised during this time and suggests that any gateway effects were not having a population level impact on smoking rates.…”
Section: Introductionmentioning
confidence: 87%
“…Having a parent figure who smokes is a well-established risk factor for smoking initiation in childhood and adolescence; a meta-analysis of 58 studies, for example, found that the odds of smoking uptake doubled where a parent figure smoked [1]. Smoking rates have declined substantially in recent years [2], with progressively comprehensive tobacco control strategies acting to de-normalise smoking [3]. However, many parents continue to smoke, with parental smoking particularly common among less affluent families [4].…”
Section: Introductionmentioning
confidence: 99%
“…We were able to explain much of this association with a relatively limited set of measured confounders and the residual effect estimates could be at least partially explained by unmeasured confounding and/or reverse causation. Taken together with other evidence such as observed increases in youth smoking after implementation of e-cigarette sale restrictions [45][46][47] and continued declines in youth pro-smoking attitudes while youth vaping has been rising [48], it seems that even if there is an effect whereby vaping increases risk for smoking, it may not be the primary or dominant explanation for these associations.…”
Section: Discussionmentioning
confidence: 94%
“…We were able to explain much of this association with a relatively limited set of measured confounders and, as noted above, the residual effect estimates could be at least partially explained by unmeasured confounding and/or reverse causation. Taken together with other evidence such as observed increases in youth smoking after implementation of e-cigarette sale restrictions [37][38][39] and continued declines in youth prosmoking attitudes while youth vaping has been rising [40], it seems that even if there is an effect whereby vaping increases risk for smoking, it is unlikely to be the primary or dominant explanation for associations between the two, and ongoing concerns about such effects should be abated.…”
Section: Meaning and Implicationsmentioning
confidence: 98%